The Construction of Women in the Short Stories Ma‘nā Al-Ḥubbi and Ḥubbun bi Lā Naslin by ‘Abbās Ḥāfiż: A Feminist Study - Nurin Amirotul Chusna; Nadya Syafira Putri (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2026)
This study aims to examine how Egyptian women are constructed in the short stories Ma‘nā al-Ḥubbi and Ḥubbun bi Lā Naslin by ‘Abbās Ḥāfiẓ througt Rosi Braidotti’s concepts of mother, monster, and machine. The research employs a qualitative method with a descriptive-analytical approach. The findings reveal that women’s identities are closely tied to domesticity, reproduction, and moral expectations within patriarchal society. First, women are constructed as mothers through expectations related to domestic skills, caregiving, and maternal affection. Their social value is associated with their ability to serve husbands, manage the household, and nurture children, even in the absence of biological motherhood. Second, women are constructed as monsters when they deviate from patriarchal norms. Female characters who reject reproductive expectations, fail to fulfill domestic roles, or violate standards of chastity are portrayed as abnormal and socially stigmatized. Third, women are constructed as machines because their existence is primarily valued through reproductive function. Women’s bodies are treated as instruments regulated by social and cultural systems concerned with childbirth, sexuality, and family continuity. Consequently, infertility or the inability to reproduce reduces women’s social value and limits their agency within marriage and family structures. Overall, the short stories reflect how patriarchal culture confines women within rigid biological and domestic roles.